The Genome of the Myxosporean Thelohanellus kitauei Shows Adaptations to Nutrient Acquisition within Its Fish Host. (8th November 2014) - Yang, Yalin; Xiong, Jie; Zhou, Zhigang; Huo, Fengmin; Miao, Wei; Ran, Chao; Liu, Yuchun; Zhang, Jinyong; Feng, Jinmei; Wang, Meng; Wang, Min; Wang, Lei; et al.
Abstract: Members of Myxozoa, a parasitic metazoan taxon, have considerable detrimental effects on fish hosts and also have been associated with human food-borne illness. Little is known about their biology and metabolism. Analysis of the genome of Thelohanellus kitauei and comparative analysis with genomes of its two free-living cnidarian relatives revealed that T. kitauei has adapted to parasitism, as indicated by the streamlined metabolic repertoire and the tendency toward anabolism rather than catabolism. Thelohanellus kitauei mainly secretes proteases and protease inhibitors for nutrient digestion (parasite invasion), and depends on endocytosis (mainly low-density lipoprotein receptors-mediated type) and secondary carriers for nutrient absorption. Absence of both classic and complementary anaerobic pathways and gluconeogenesis, the lack of de novo synthesis and reduced activity in hydrolysis of fatty acids, amino acids, and nucleotides indicated that T. kitauei in this vertebrate host–parasite system has adapted to inhabit a physiological environment extremely rich in both oxygen and nutrients (especially glucose), which is consistent with its preferred parasitic site, that is, the host gut submucosa. Taking advantage of the genomic and transcriptomic information, 23 potential nutrition-related T. kitauei -specific chemotherapeutic targets were identified. This first genome sequence of a myxozoan will facilitate development of potential therapeutics for efficient control of myxozoan parasites and ultimately prevent myxozoan-induced fish-borne illnesses in humans.